Modeling of Carbon Monoxide Two-Photon Laser-Induced Fluorescence (LIF) Spectra at High Temperature and Pressure. Issue 6 (June 2020) - Carrivain, Olivier; Orain, Mikael; Dorval, Nelly; Morin, Céline; Legros, Guillaume
In this study, quantitative model of two-photon excitation and fluorescence spectra of carbon monoxide based on up-to-date spectroscopic constants collected during an extensive literature survey was developed. This semi-classical model takes into account Hönl–London factors, quenching effects (collisional broadening and shift), ionization and stark effect (broadening and shift), whereas predissociation is neglected. It was specifically developed to first reproduce with a high confidence level the behavior of our experimental spectra obtained from laser-induced fluorescence (LIF) measurements, and then to allow us to extrapolate the fluorescence signal amplitude in other conditions than those used in these experiments. Synthetic two-photon excitation and fluorescence spectra of CO were calculated to predict the fluorescence signal at high pressures and temperatures, which are representative of gas turbine operating conditions. Comparison between experimental and calculated spectra is presented. Influence of temperature on both excitation and fluorescence spectra shapes and amplitudes is well reproduced by the simulated ones. It is then possible to estimate flame temperature from the comparison between experimental and calculated shapes of numerical excitation spectra. Influence of pressure on both excitation and fluorescence spectra was also investigated. Results show that for temperature below 600 K and pressure above 0.1 MPa, the usual Voigt profile is not suitable to reproduce the shape of the excitation spectrum. We found that the Lindholm profile is well suited to reproduce the pressure-dependence of the spectrum in the range 0.1 to 0.5 MPa at 300 K, and 0.1 to 0.7 MPa at 860 K. Beyond 0.7 MPa, in this temperature range, it is shown that the Lindholm profile does no longer match the spectral profiles, in particularly the red wing. Further analyses taking into account the line mixing phenomenon at higher pressure are thus discussed.